Adaptive servo sensitivity control algorithm for EDM of shrouded blisks - Sun, Yan-Xin; Xi, Xue-Cheng; Zhao, Wan-Sheng (International journal of advanced manufacturing technology, 2024)
Multi-axis electrical discharging machining (EDM) is the most commonly used manufacturing method for shrouded blisks. The discharge points and discharge gap distance are time-varying in a multi-axis EDM process. It is difficult to obtain an optimal servo feedrate. In traditional multi-axis EDM servo control systems, servo sensitivity is usually chosen as a smaller constant to avoid arc discharges. Thus, the servo feedrate is lower than the material removal rate in a machining process. The open circuit rate is high and the machining efficiency is decreased. This paper proposes an adaptive servo sensitivity control algorithm for multi-axis EDM of shrouded blisks. Servo sensitivity is adjusted according to discharge status, so as to decrease the open circuit rate and to improve the machining efficiency. Experiment results show that the proposed adaptive servo sensitivity control algorithm can improve the machining efficiency of shrouded blisks by 28.02% without deteriorating surface integrity.